Use of a wireless NIRS monitor to track changes in muscle oxygenation for laboratry-based nordic skiing test protocols - Cornachione, K.; McLaren, J.; Heil, D. P. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Near-infrared spectroscopy (NIRS) is a non-invasive imaging technique that has been used to measure muscle oxygen saturation (SmO2, %). Despite the availability of this technology for decades, the use of NIRS-based monitors for monitoring changes in SmO2 for cross country (XC) skiers training and racing has been very limited.